Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Perusahan Daerah Air Minum (PDAM) - Gledis Liensky; Jondry A. Hetharie (Univiversitas Dr. Djar Wattiheluw, 2022)
This research entiled the effect of service quality on customer satisfaction at PDAM Dobo city. Based on problems related to customer satisfaction in this case related to the quality of service that has not been optimal. The aim of this study is to determine the effect of tangible, responsiveness, reliability, assurance, dan emphaty on user satisfaction of PDAM kota Dobo. The population oh this research are all customers of PDAM Dobo City with a total sample of 76 respondents. The data collection method is the questionnaire method. The validity unit uses total correlation, while the reliability test uses Cronbach alpha. The classical assumption test includes the normality test, the linearity test, the multicollinearity test, and the heteroscedasticity test, test t and test F. The results of this study indicate that (1) There is a positive and significant effect of Tangibles on customer Satisfaction at PDAM City of Dobo (2) There is a positive and significant effect of Responsiveness on Customer Satisfaction in PDAM City of Dobo (3) There is a positive and significant effect of Reliability on Customer Satisfaction in PDAM City of Dobo (4) There is a positive and significant influence of Assurance on Customer Satisfaction at PDAM City of Dobo (5) There is a positive and significant influence of Emphaty on Customer Satisfaction at PDAM city of Dobo.